PENGARUH KEPEMILIKAN MANAJERIAL DAN KUALITAS AUDITOR EKSTERNAL TERHADAP NILAI PERUSAHAAN - Poerwati, Liza (UNIB Press, 2018)
This study aimed to investigate the influence of managerial ownership and quality eksternal auditor on firm value. Firm value in this study is proxied by Tobin'S Q. The sample was selected from manufacture companies were listed on Indonesia Stock Exchange in 2005 until 2009 using a Quota Random sampling method. The method of analysis of this study used linear regression. The Result of this study show both ownership managerial auditor and quality auditor eksternl have an effect on to firm value. Ownership managerial have an effect on negative and significant. Quality auditor eksternal have an effect on positive and significant.